Structural Processing for Wireless Communications - Lu, Jianhua. (SpringerBriefs in Electrical and Computer Engineering, 2015)
This brief presents an alternative viewpoint on processing technology for wireless communications based on recent research advances. As a lever in emerging processing technology, the structure perspective addresses the complexity and uncertainty issues found in current wireless applications. Likewise, this brief aims at providing a new prospective to the development of communication technology and information science, while stimulating new theories and technologies for wireless systems with ever-increasing complexity. Readers of this brief may range from graduate students to researchers in related fields.